2013
DOI: 10.1002/jmv.23614
|View full text |Cite
|
Sign up to set email alerts
|

Rhinoviruses as an underestimated cause of influenza‐like illness in pregnancy during the 2009–2010 influenza pandemic

Abstract: During the 2009-2010 influenza pandemic, pregnant women were identified at high risk for severe infection. In case of influenza-like illness they were systematically treated with oseltamivir. When performed, virological diagnosis showed that some of these women were not influenza-infected. The objectives of the study were to identify viruses which could induce an influenza-like illness in pregnant women during the 2009-2010 pandemic, then to establish possible links between detected viruses and symptoms, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The influenza test was generally performed using specific PCR, but in five cases, multiplex PCR was performed, detecting two positive cases for rhinoviruses. Two retrospective studies conducted during the 2009–2010 flu pandemic found in pregnant women with influenza-like symptoms, non-influenza respiratory viruses rates of 23 %, and influenza H1N1 rates between 31 and 42 %, similar to our results [ 10 , 11 ]. The multiplex PCR was not used on a routine basis because it is expensive and time-consuming, although this strategy could possibly avoid use of antibiotics and hospitalizations.…”
Section: Discussionsupporting
confidence: 91%
“…The influenza test was generally performed using specific PCR, but in five cases, multiplex PCR was performed, detecting two positive cases for rhinoviruses. Two retrospective studies conducted during the 2009–2010 flu pandemic found in pregnant women with influenza-like symptoms, non-influenza respiratory viruses rates of 23 %, and influenza H1N1 rates between 31 and 42 %, similar to our results [ 10 , 11 ]. The multiplex PCR was not used on a routine basis because it is expensive and time-consuming, although this strategy could possibly avoid use of antibiotics and hospitalizations.…”
Section: Discussionsupporting
confidence: 91%
“…Rhinovirus, coronavirus, parainfluenza viruses 1-4, and human metapneumovirus have also recently been detected in cases of respiratory viral infections in pregnant women [21,22]. Rhinovirus is described as a cause of influenza-like illness in several studies in pregnant women, and Middle Eastern Respiratory Syndrome and Severe Acute Respiratory Syndrome coronaviruses have been shown in case reports to be associated with severe disease in pregnant women [23,24]. Other respiratory viruses were commonly detected in Nepal in women with fever and respiratory symptoms, with the most common being rhinovirus [22].…”
Section: Concepts Of Maternal Immunizationmentioning
confidence: 99%
“…However, recently researchers shifted to directly sequencing the cDNA product after purification. Most articles published within the last year that sequenced RV utilized this method (Daleno et al, 2013; Garcia et al, 2013; Miyaji et al, 2013; Pilorge et al, 2013). Others utilized direct sequencing in earlier studies as well (Blomqvist et al, 2009; Kneider et al, 2009; Wisdom et al, 2009; Mizuta et al, 2010; Watanabe et al, 2010).…”
Section: Introductionmentioning
confidence: 99%